2005
DOI: 10.1111/j.1440-1819.2005.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal overprotection in obsessive‐compulsive disorder and depression with obsessive traits

Abstract: Previous studies have indicated that a parental rearing style showing a low level of care on the parental bonding instrument (PBI) is a risk factor for depression, and that there is a relationship between the overprotective rearing style on the PBI and obsessive-compulsive disorder (OCD). However, there is no study on the parental rearing attitudes in depressive patients divided into two groups based on their obsessive traits. In this study, we evaluated the parental rearing attitudes and examined the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…These results have been further supported by later studies investigating perceived parenting in individuals with anxiety disorders (Silove, Parker, Hadzi-Pavlovic, & Manicavasagar, 1991;Wilborg & Dahl, 1997). However, some of these studies only found differences between participants with anxiety disorders and healthy controls on either the care (Alonso et al, 2004;Pacchierotti et al, 2002) or the control dimension (Hafner, 1988;Turgeon, O'Connor, Marchand, & Freeston, 2002;Yoshida, Taga, Matsumoto, & Fukui, 2005). Recent large-scale epidemiological surveys, using either a full or an abbreviated version of the PBI, have further supported the assumption that adults' retrospective reports of lack of parental care are more consistently associated with both mood and anxiety disorders than parental control.…”
Section: Introductionmentioning
confidence: 48%
“…These results have been further supported by later studies investigating perceived parenting in individuals with anxiety disorders (Silove, Parker, Hadzi-Pavlovic, & Manicavasagar, 1991;Wilborg & Dahl, 1997). However, some of these studies only found differences between participants with anxiety disorders and healthy controls on either the care (Alonso et al, 2004;Pacchierotti et al, 2002) or the control dimension (Hafner, 1988;Turgeon, O'Connor, Marchand, & Freeston, 2002;Yoshida, Taga, Matsumoto, & Fukui, 2005). Recent large-scale epidemiological surveys, using either a full or an abbreviated version of the PBI, have further supported the assumption that adults' retrospective reports of lack of parental care are more consistently associated with both mood and anxiety disorders than parental control.…”
Section: Introductionmentioning
confidence: 48%
“…Family environment and parenting practices, including overprotection, high levels of parental control, rejection, and a lack of parental warmth, have been reported in youth with OCD [17,18]. Similar family characteristics have been reported in youth with depression.…”
mentioning
confidence: 54%
“…This finding was similar to our recent study [24], indicating that OCD symptoms in Cyprus were significantly higher relative to other European countries. There is no clear explanation for this finding although it could be related to Cypriot's over-controlling parental child-rearing practices [48] and excessive fear of contamination. Additionally, individual characteristics [e.g., perfectionism; 49] and strong religious culture [48] could explain this heightened OCD.…”
Section: Discussionmentioning
confidence: 89%
“…There is no clear explanation for this finding although it could be related to Cypriot's over-controlling parental child-rearing practices [48] and excessive fear of contamination. Additionally, individual characteristics [e.g., perfectionism; 49] and strong religious culture [48] could explain this heightened OCD. Alternatively it could be that the items of the Greek translation of SCAS that tap OCD might have been viewed by the Greek Cypriot children as more socially acceptable relative to the items that tap the other scales.…”
Section: Discussionmentioning
confidence: 89%